Does the Information Processing Requirements and Supply Chain Practices Effect the Imperativeness of an Agile Supply Chain Strategy for the Supply Chain Performance? - Sami Mohamed AlHaderi (International Journal of Supply Chain Management, 2019)
This research study aims at explaining the way in which supply chain performance can be improved by agile supply chain strategy. The phenomenon has been studied from theoretical perspective. A key aspect is the complementary association between supply chain practices and supply chain strategy. It has been suggested that agile supply chain strategy can be supported by specific supply chain practices through a positive relation between supply chain performance and agile supply chain strategy. The second aspect is the firm’s information processing. Through this aspect, it can be examined whether the agile capability of information system improves the influence of supply chain practices as a mediator. The study has used the survey-based methodology to achieve the objective of the current study. The data is collected from the manufacturing firms in Kingdom of Saudi Arabia. The benefits of supply chain practices have been enhanced through IS capability by the creation of match between the abilities and needs of information processing. The influence of supply chain practices as a mediator between the relation of supply chain performance and agile supply chain is improved with ‘information system capability for agility. The relation between supply chain performance and agile supply chain strategy is positively mediated when the firm can deliver a range of products quickly. In order to deliver the required number of products, it is important to forecast the demand in an accurate way.